The effect of high‐flow nasal oxygen on hospital length of stay in cardiac surgical patients at high risk for respiratory complications: a randomised controlled trial1. (18th July 2018) - Zochios, V.; Collier, T.; Blaudszun, G.; Butchart, A.; Earwaker, M.; Jones, N.; Klein, A. A.
Summary: There has been increased interest in the prophylactic and therapeutic use of high‐flow nasal oxygen in patients with, or at risk of, non‐hypercapnic respiratory failure. There are no randomised trials examining the efficacy of high‐flow nasal oxygen in high‐risk cardiac surgical patients. We sought to determine whether routine administration of high‐flow nasal oxygen, compared with standard oxygen therapy, leads to reduced hospital length of stay after cardiac surgery in patients with pre‐existing respiratory disease at high risk for postoperative pulmonary complications. Adult patients with pre‐existing respiratory disease undergoing elective cardiac surgery were randomly allocated to receive high‐flow nasal oxygen (n = 51) or standard oxygen therapy (n = 49). The primary outcome was hospital length of stay and all analyses were carried out on an intention‐to‐treat basis. Median (IQR [range]) hospital length of stay was 7 (6–9 [4–30]) days in the high‐flow nasal oxygen group and 9 (7–16 [4–120]) days in the standard oxygen group (p=0.012). Geometric mean hospital length of stay was 29% lower in the high‐flow nasal group (95%CI 11–44%, p = 0.004). High‐flow nasal oxygen was also associated with fewer intensive care unit re‐admissions (1/49 vs. 7/45; p = 0.026). When compared with standard care, prophylactic postoperative high‐flow nasal oxygen reduced hospital length of stay and intensive care unit re‐admission. This is the first randomised controlled trial examining the effect of prophylactic high‐flow nasal oxygen use on patient‐centred outcomes in cardiac surgical patients at high risk for postoperative respiratory complications.